The Language of Musta'rab Jews: The Names of the Holidays in Peqtʿin as a Test Case. (15th February 2018) - Henshke, Yehudit
Abstract: This article treats the Arabic-Hebrew interlingual contact that emerges from examination of the language of the Musta'rab community in Israel. Based on a linguistic field study carried out among the Jews of Peqi'in, it examines a unique phenomenon in their spoken dialect: the penetration of Arabic and Islamic terms into the Jewish religious sphere as exemplified in their designations for the Jewish holidays. This study shows that the Jews of Peqi'in preferred the Arabic names of the holidays to the Hebrew ones; some of these names are ancient and are attested in medieval Jewish texts; others are late. It also shows that some of their Judaeo-Arabic expressions are identical to those used by their non-Jewish neighbours. Moreover, Peqi'in Jews do not hesitate to use the designations for the non-Jewish holidays. Their adherence to Arabic is also exemplified by the use of unique Arabic words and expressions, not found in the surrounding dialects, which carry specifically Jewish meanings. Another intriguing finding was that the Jewish dialect of Peqi'in has preserved unique Arabic configurations not found in the general spoken Arabic dialect. The roots of this phenomenon's anomalous nature, as compared to what is known of other Jewish communities, probably lie in the preservation in the vernacular of Peqi'in Jews of an ancient path in use in medieval Judaeo-Arabic in the Fertile Crescent.